Synthesis, Characterization, Docking and Study of Inhibitory Action of Some Novel C‐Alkylated Chalcones on 5‐LOX Enzyme. Issue 28 (2nd October 2017) - Kasthuri, Jyothi Kumari; Singh Jadav, Surender; Thripuram, Vijaya Durga; Gundabolu, Usha Rani; Ala, Vasu babu; Kolla, Jayaprakash Narayana; Jayaprakash, Venkatesan; Ahsan, Mohamed Jawed; Bollikolla, Hari Babu
Abstract: A series of C‐alkylated chalcones on ring 'B' of C6 ‐C3 ‐C6 system of the basic flavonoid skeleton were synthesized by taking different alkyl substituted aldehydes by conventional approaches. The compounds (5 a‐l ) were obtained by condensing di‐ O ‐methylated phloroacetophenone with various alkylated (methyl, di‐methyl, ethyl and n‐propyl) substituted aromatic aldehydes (4 a‐l ) and characterized by different spectroscopic methods (IR, NMR, LC–MS and elemental analysis) and further studied their inhibitory action on 5‐lipoxygenase (5‐LOX) enzyme. The compounds (E)‐3‐(4‐ethoxy‐5‐methoxy‐2‐methylphenyl)‐1‐(2‐hydroxy‐4, 6‐dimethoxyphenyl) prop‐2‐en‐1‐one (5 k ), (E)‐3‐(2, 4‐dimethoxy‐5‐methylphenyl)‐1‐(2‐hydroxy‐4, 6‐dimethoxy phenyl)prop‐2‐en‐1‐one (5 i ), (E)‐3‐(4, 5‐dimethoxy‐2‐methylphenyl)‐1‐(2‐hydroxy‐4, 6‐dimethoxyphenyl)prop‐2‐en‐1‐one (5 j ), and (E)‐1‐(2‐hydroxy‐4, 6‐dimethoxyphenyl)‐3‐(2‐methoxy‐4, 5‐dimethylphenyl)prop‐2‐en‐1‐one (5 l ) showed a significant 5‐LOX enzyme inhibitory action with IC50 ranging between 49.1 and 52.3  μ M, whereas positive control curcumin exhibited IC50 of 22  μ M. The molecular docking simulation study revealed that the compounds were well accommodated in the allosteric site of the enzyme, 5‐LOX. Abstract : The investigation describes the development of a novel class of C‐alkyl substituted chalcones viz . C‐methyl, C‐di‐methyl, C‐ethyl, and C‐propyl on "B" ring of basic flavonoid skeleton towards potential anti‐inflammatory compounds. The results of the 5‐LOX inhibition studies on a total of 12 designed and synthesized compounds revealed that the substitutions such as methoxy/ethoxy at para ‐position and ortho ‐position might be a significant factor for 5‐LOX activity of chalcones. The molecular docking study on the designed chalcones revealed their potent lipoxygenase inhibitory activity.